(untitled) (Majalah Kedokteran Bandung, 2025)
The shift in global epidemiology has significantly increased the prevalence of non-communicable diseases, positioning stroke as one of the primary contributors to both disability and vascular-related mortality worldwide, with a notable impact observed in Asia. This research endeavours to explore the correlation between various stroke risk factors and the occurrence of lacunar stroke at Dr Soebandi Regional Hospital, Jember, Indonesia. Employing a cross-sectional correlational design, the study drew upon data extracted from medical records of 41 patients who had experienced a first-time ischemic stroke between 2022 and 2023. The primary variables under investigation were gender, age, hypertension, diabetes mellitus, dyslipidaemia, and heart disease. Statistical analysis conducted with Chi-square test indicated a significant association between hypertension and diabetes mellitus, with both conditions linked to an 11-fold increased risk of lacunar stroke compared to having only one condition. In contrast, factors such as age, gender, dyslipidaemia, and heart disease did not exhibit significant associations. These results emphasize the imperative for rigorous management of hypertension and diabetes to reduce the risk of lacunar stroke.